Anti-Inflammatory Effects of the Chinese Herbal Formula Sini Tang in Myocardial Infarction Rats. (3rd March 2014) - Liu, Jiangang; Peter, Karoline; Shi, Dazhuo; Zhang, Lei; Dong, Guoju; Zhang, Dawu; Breiteneder, Heimo; Bauer, Rudolf; Jakowitsch, Johannes; Ma, Yan
Abstract : The aim of this study was to evaluate the anti-inflammatory profiling of the Chinese herbal formula Sini Tang (SNT) in myocardial infarction (MI) rats. SNT, a decoction consisting of four herbs: Aconitum carmichaelii, Cinnamomum cassia, Zingiber officinale, and Glycyrrhiza uralensis, was characterized as a remedy to treat syndromes corresponding to heart failure and MI in China. Potential biomarkers, which reflect the extent of myocardial necrosis and correlate with cardiac outcomes following MI, such as atrial natriuretic peptide (ANP), high sensitivity C-reactive protein (hs-CRP), and proinflammatory cytokines such as tumor necrosis factor- α, interleukin-6, and interleukin-1 β (TNF- α, IL-6, and IL-1 β ) were determined in plasma, serum, and in myocardial tissue of MI rats after treatment with SNT. Our data indicate that SNT decreased significantly the levels of hs-CRP, TNF- α, IL-6, and IL-1 β in MI rats. SNT decreased the expression of ANP levels in plasma and increased the vascular active marker nitric oxide, which limits vascular inflammation. In addition, SNT could decrease the expression of endothelin-1 levels in rat plasma post-MI. Our data suggest that the Chinese herbal formula SNT has the potential to improve cardiac function after MI. SNT may be a candidate for treating MI and its associated inflammatory responses.